2020
DOI: 10.1167/iovs.61.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing After Alkali Burn Injury of the Cornea Involves Nox4-Type NADPH Oxidase

Abstract: Purpose Corneal injury that occurs after burning with alkali initiates wound-healing processes, including inflammation, neovascularization, and fibrosis. Excessive reactions to injury can reduce corneal transparency and thereby compromise vision. The NADPH oxidase (Nox) enzyme complex is known to be involved in cell signaling for wound-healing angiogenesis, but its role in corneal neovascularization has been little studied. Methods The center corneas of wild-type and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Normally, alkali solutions tend to penetrate the cornea rapidly causing destruction of the stromal proteoglycan ground substance and thus, increasing the collagen fibril density, which leads to tissue stiffening [2,58,59]. The relative increase of Young's modulus 14 days postburn could be due to the development of chronic inflammation, neovascularization, and, most importantly, the increased fibrotic response associated with the wound healing process [16,56]. During the early repair phase (i.e., 8-20 days postburn) of the wound healing process, the normal structural elements of the stroma are replaced by excessive accumulation of the ECM matrix and distorted distribution of collagen fibers, resulting in fibrosis which is characterized by scarring and stiffening of tissue [2,16,56,60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, alkali solutions tend to penetrate the cornea rapidly causing destruction of the stromal proteoglycan ground substance and thus, increasing the collagen fibril density, which leads to tissue stiffening [2,58,59]. The relative increase of Young's modulus 14 days postburn could be due to the development of chronic inflammation, neovascularization, and, most importantly, the increased fibrotic response associated with the wound healing process [16,56]. During the early repair phase (i.e., 8-20 days postburn) of the wound healing process, the normal structural elements of the stroma are replaced by excessive accumulation of the ECM matrix and distorted distribution of collagen fibers, resulting in fibrosis which is characterized by scarring and stiffening of tissue [2,16,56,60].…”
Section: Discussionmentioning
confidence: 99%
“…The relative increase of Young's modulus 14 days postburn could be due to the development of chronic inflammation, neovascularization, and, most importantly, the increased fibrotic response associated with the wound healing process [16,56]. During the early repair phase (i.e., 8-20 days postburn) of the wound healing process, the normal structural elements of the stroma are replaced by excessive accumulation of the ECM matrix and distorted distribution of collagen fibers, resulting in fibrosis which is characterized by scarring and stiffening of tissue [2,16,56,60]. Different from the results of the current study, uniaxial tensile testing on porcine corneas demonstrated weakening of alkali-lesioned and cultured tissues compared with their healthy and fresh counterparts on day 7 post-AB [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the well-established AB mouse model to assess the change in GAG composition during corneal wound healing 5 and 14 days after a chemical injury. This model leads to inflammatory cell infiltration and corneal scarring, and the loss of transparency is evident at both 5 and 14 days after AB [ 56 , 57 , 58 , 59 , 60 ]. Disaccharide analysis revealed there was a significant increase in CS expression after AB, and, thus, CSPGs are important constituents of the provisional matrix in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The acute corneal alkali-induced wounding of rats was performed as previously described ( Choi et al, 2017 ; Hakami et al, 2020 ). At the beginning of the study, randomization was performed based on body weight prior to the induction of the injury.…”
Section: Methodsmentioning
confidence: 99%